2015
DOI: 10.1242/bio.201411114
|View full text |Cite
|
Sign up to set email alerts
|

Rab40C is a novel Varp-binding protein that promotes proteasomal degradation of Varp in melanocytes

Abstract: Varp (VPS9-ankyrin repeat protein) was originally identified as an activator of small GTPase Rab21 through its VPS9 domain, but it has subsequently been shown to function as a Rab32/38 effector through its first ANKR1 domain. Although these functions of Varp are important for melanogenesis, Varp contains a second ANKR2 domain, whose function remained completely unknown. Here we identified Rab40C, an atypical Rab containing a SOCS box that recruits a ubiquitin ligase complex, as a novel ANKR2-binding protein an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 48 publications
4
31
0
Order By: Relevance
“…However, galectin 8 binding is not required for NDP52 recruitment to GAS, in contrast to the cellular response against Salmonella. We note that a similar observation was recently reported for Rab40C, overexpression and knockdown of which both repressed production of melanin (Yatsu et al, 2015). Importantly, these experiments also demonstrated that Rab35 and its inactivation by TBC1D10A regulate autophagosome biogenesis by recruiting NDP52 to invading bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…However, galectin 8 binding is not required for NDP52 recruitment to GAS, in contrast to the cellular response against Salmonella. We note that a similar observation was recently reported for Rab40C, overexpression and knockdown of which both repressed production of melanin (Yatsu et al, 2015). Importantly, these experiments also demonstrated that Rab35 and its inactivation by TBC1D10A regulate autophagosome biogenesis by recruiting NDP52 to invading bacteria.…”
Section: Discussionsupporting
confidence: 88%
“…A) Schematic representation of VARP and its ligand binding sites. The VPS9 domain, ANKR1 domain, ANKR2 domain, VID domain and two Cys‐rich regions are responsible for GDP‐Rab21 binding , GTP‐Rab32/38 binding , GTP‐Rab40C binding , VAMP7 binding and VPS29 binding , respectively. The precise KIF5A, GOLGA4 and VPS35 binding sites have not yet been determined .…”
Section: Domain Organization Of Varpmentioning
confidence: 99%
“…Consequently, beads coupled with the recombinant ANKR1 domain are a useful tool for trapping active Rab32/38 in cell lysates , and when the ANKR1 domain is expressed in melanocytes, it functions as a ‘GTP‐Rab32/38 trapper’ that specifically inhibits the function of Rab32/38 . Although the ANKR1 domain and ANKR2 domain exhibit more than 60% amino acid similarity, the ANKR2 domain of VARP does not recognize Rab32/38, and instead specifically binds to the GTP‐bound active form of Rab40 subfamily members . However, the ANKR2 domain is unlikely to function as a Rab40 effector domain, and Rab40 promotes proteasomal degradation of VARP by recruiting an E3 ubiquitin ligase complex via its SOCS domain (; see next section for details).…”
Section: Varp‐binding Partnersmentioning
confidence: 99%
“…Rab22B/31 (Kajiho et al, 2011) 4 ALS2 ANKRD27 (84079) Varp Rab21 (Zhang et al, 2006) 2,3 (Tamura et al, 2011) 3 Rab32 (Tamura et al, 2009) Rab38 (Wang et al, 2008) VAMP7 (Burgo et al, 2009) VPS29 (Hesketh et al, 2014) VPS35 (McGough et al, 2014) Rab40 (Yatsu et al, 2015) RACK1 (Marubashi et al, 2016b) VPS9D1 ( Rab8 (Hattula et al, 2002) 1,2,3…”
Section: Ishida Et Almentioning
confidence: 99%
“…Rab21-activation by Varp and its interaction with VAMP7 cooperate to regulate neurite outgrowth of both PC12 cells and mouse hippocampal neurons and dendrite outgrowth of melanocytes (Burgo et al, 2009(Burgo et al, , 2012Ohbayashi et al, 2012). Varp is also involved in melanogenic enzyme transport to melanosomes, which are known as lysosome-related organelles, through interaction with Rab32 and Rab38 via the ANKR1 domain (Tamura et al, 2009(Tamura et al, , 2011 and with Rab40C via the ANKR2 domain (Yatsu et al, 2015). Moreover, Varp interacts with two subunits of the retromer complex (VPS29 and VPS35) and is involved in the endosome-to-plasma-membrane recycling of certain transmembrane proteins (Hesketh et al, 2014;McGough et al, 2014).…”
Section: Rab-gefs and Their Target Rabsmentioning
confidence: 99%